The impact of fourth industrial revolution era on Nigeria’s counterterrorism strategy towards Boko Haram movement - Akwen, Gabriel Tyoyila; Ravichandran Moorthy,; Sity Daud, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The emergence of the fourth industrial revolution (4IR) is both thrilling and frightening. The technology under this era would have an impact on mankind. The 4IR has the potentials of increasing income heights through new entrepreneur innovations. The new technologies under 4IR will improve productivity and reduce the cost of communication and transportation. On the one hand, there are numerous gains of the 4IR, on the other hand, there are also many challenges associated with it. With particular reference to security, it is feared that the 4IR could pave the way to greater insecurity, particularly when it is used by terrorists like Boko Haram to carry out their attacks. The main argument of this paper is that the non-deployment of 4IR technologies in countering Boko Haram terrorism is a major hindrance to Nigeria’s war against terrorism. The major objective of this study is to investigate how the use of 4IR technologies have enhanced the activities of Boko Haram terrorist and Nigerian counterterrorism operatives. The data for this research were sourced through secondary sources and analyzed by the use of the qualitative method. The strategic theory was espoused as the framework of analysis. The research discovered that the sophistication in the activities of Boko Haram is bone out of the utilization of the 4IR technologies in their operations. The 4IR enable the terrorist to seek assistance from renowned terrorist groups and acquire state-of-the-art weapons and training. The paper further reveals that the Nigerian counterterrorism initiative is not effective in curbing the Boko Haram attacks partly because it is premised around the third industrial revolution technologies. This research recommends 4IR technology compliance as the first step to match the Boko Haram onslaught before the use of soft power.